2016
DOI: 10.1002/chem.201503543
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Aptamer‐Based Functional Probes for Bioanalysis and Biomedicine

Abstract: Nucleic acid aptamers are short synthetic DNA or RNA sequences that can bind to a wide range of targets with high affinity and specificity. In recent years, aptamers have attracted increasing research interest due to their unique features of high binding affinity and specificity, small size, excellent chemical stability, easy chemical synthesis, facile modification, and minimal immunogenicity. These properties make aptamers ideal recognition ligands for bioanalysis, disease diagnosis, and cancer therapy. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 154 publications
0
41
0
1
Order By: Relevance
“…First, it has been reported that natural nucleic acids do not possess the full spectrum of chemical functional groups and conformational space needed to yield high-quality aptamers for many proteomic targets. To solve this problem, a number of methods (e.g., Hi-Fi SELEX (Ouellet et al, 2015), array-based strategies (Cho et al, 2015) and multiparameter particle display strategies ) have been developed, which have led to greater selection efficiencies (Zhang et al, 2016). In this light, chemical methods for DNA synthesis have enabled the incorporation of special functional groups onto oligonucleotides and have led to a significant advancement in the number of diverse aptamers that are available (Kimoto et al, 2013).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…First, it has been reported that natural nucleic acids do not possess the full spectrum of chemical functional groups and conformational space needed to yield high-quality aptamers for many proteomic targets. To solve this problem, a number of methods (e.g., Hi-Fi SELEX (Ouellet et al, 2015), array-based strategies (Cho et al, 2015) and multiparameter particle display strategies ) have been developed, which have led to greater selection efficiencies (Zhang et al, 2016). In this light, chemical methods for DNA synthesis have enabled the incorporation of special functional groups onto oligonucleotides and have led to a significant advancement in the number of diverse aptamers that are available (Kimoto et al, 2013).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Although antibody combinations can help to decipher these activating KIRs,187, 192, 201 they do not allow analysis at single KIR level because of antibody cross‐reactivity. Aptamers, short single‐stranded nucleic acid oligomers that bind to a specific target molecule, with their unique features of high binding affinity and specificity, could offer a useful alternative to antibodies in discriminating subtly different forms of KIR 209. Improving KIR repertoire analysis will contribute to our understanding of clinical situations where KIR have a proven or suspected role such as antiviral immune response, transplantation, autoimmunity and reproduction.…”
Section: Kir Gene Expressionmentioning
confidence: 99%
“…One approach is the utilization of drug delivery systems, where drugs are combined with carriers like micelles, liposomes, or nanoparticles to transport the drug to the target tissue . These carrier systems usually have sizes between 10 and 200 nm . The determined size limit of particles for internalization into cells via receptor‐mediated endocytosis was 200 nm, consequently the size of carriers should not exceed this size if particles are to be internalized by this uptake route .…”
Section: Introductionmentioning
confidence: 99%
“…The determined size limit of particles for internalization into cells via receptor‐mediated endocytosis was 200 nm, consequently the size of carriers should not exceed this size if particles are to be internalized by this uptake route . Furthermore, the size between 10 and 200 nm limits the penetration through the endothelial cells in healthy vasculature, but the leaky vasculature in solid tumors enables enrichment of particles in the tumor tissue . This effect is called enhanced permeability and retention effect .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation